1991
DOI: 10.1017/s0031182000062594
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between faecal egg count and worm burden of Opisthorchis viverrini in human autopsy cases

Abstract: The relationship between faecal examination for egg output and worm burden of Opisthorchis viverrini in man of 181 autopsy cases from Northeast Thailand is described. Diagnosis of the parasite infection by stool examination for the presence of eggs was less sensitive than the worm recovery technique. Using Stoll's dilution and formalin-ether technique, no eggs were detected in the faeces of 20 cases harbouring low worm burdens (less than 20 worms). The quantitative faecal egg count by Stoll's dilution techniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
68
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(78 citation statements)
references
References 17 publications
(16 reference statements)
6
68
1
Order By: Relevance
“…When the density of the worms was high, the egg production was high. Similar results in a study on Opisthorchis viverrini were obtained by Sithithaworn et al (1991).…”
Section: Discussionsupporting
confidence: 89%
“…When the density of the worms was high, the egg production was high. Similar results in a study on Opisthorchis viverrini were obtained by Sithithaworn et al (1991).…”
Section: Discussionsupporting
confidence: 89%
“…Very similar linear regression lines were described in Thailand. 33,34 Hence, we can confirm that egg counts are a valid proxy measure for intensity of infection with O. viverrini. In addition, similar to Elkins et al, 33 we also found a decreasing fecundity of O. viverrini with increasing worm burden, a phenomenon that may reflect density-dependent constraints on fecundity.…”
Section: Discussionsupporting
confidence: 58%
“…In addition, similar to Elkins et al, 33 we also found a decreasing fecundity of O. viverrini with increasing worm burden, a phenomenon that may reflect density-dependent constraints on fecundity. 34,35 Our validation of a commonly employed faecal concentration technique with results of the purging examination, the latter serving as a diagnostic 'gold standard', showed high sensitivity and specificity for diagnosis both of O. viverrini and MIFs. Our findings therefore support the use of FECT in future studies emphasising parasite speciesspecific diagnosis.…”
Section: Discussionmentioning
confidence: 88%
“…The finding of PCR positive results in egg-negative samples is in concordance with the monoclonal-antibody-based coproantigen detection method, which also demonstrated positive reactions in eggnegative cases (11). Moreover, in an autopsy study, only 30% of the people who harbored fewer than 10 adult O. viverrini worms excreted eggs that were detectable in their feces while the majority of them (70%) were egg negative (13). That we obtained PCR-positive results with apparently egg-negative samples suggests that diagnosis by our PCR method is more sensitive than the fecal examination method, particularly in the light infection group.…”
supporting
confidence: 73%